Polish Emergency Dispatchers During a COVID-19 Pandemic – Burnout Syndrome, Perceived Stress, and Self-Efficacy. Effects of Multidimensional Path Analysis - Makara-Studzińska, Marta; Załuski, Maciej; Adamczyk, Katarzyna (Frontiers in Psychology, 2021)
International research has demonstrated that emergency call operators face unique risks to their mental health, in particular job stress and occupational burnout syndrome. There is already wide knowledge about the relationship between stress, burnout and employee personal resources, which has practical application in preventing mental health. However, more research into the subtle relationships between variables is needed. The aim of the study was to check the moderation effect of differences in the intensity of latent variables on the relationship between perceived stress, self-efficacy and professional burnout. The participants were 546 call-takers and dispatchers from 14 public-safety answering point in Poland aged between 19-65 years. The Link Burnout Questionnaire, the 10-item Perceived Stress Scale, the Generalized Self-Efficacy Scale, and an independent questionnaire were used to gather information. The method of path analysis was used. The study confirmed the existence of negative relationships between perceived stress (assessment of the current situation) and self-efficacy (a personal trait). Taking into account the moderating effect of latent variable: psychological comfort revealed a hidden relationship between stress and burnout. The stress-burnout relationship occurred only among participants with low level of psychological comfort, so it was not a proportional relationship. In the case of participants with a high level of second latent variable: power-to-affect, the hypothesis that a high level of this variable should weaken the relationship between stress and burnout was not confirmed. The level of latent variables did not affect the self-efficacy relationship with occupational burnout. Taking into account the differences in the intensity of latent variables showed their moderating effect, which often turned out to be different from the assumed one and obtained in the research of other authors. This allowed to discover the relationships that might otherwise have been overlooked and not included in burnout prevention. The results showed a high level of occupational burnout in the ECD's group during the COVID-19 pandemic: 32% of the responders reported emotional exhaustion, 53% loss of professional effectiveness.